The Relationship between Emotional Intelligence and Pain Management Awareness among Nurses - Issa M.R.; Muslim N.A.; Alzoubi R.H.; Jarrar M.; Alkahtani M.A.; Al-Bsheish M.; Alumran A.; Alomran A.K. (MDPI, 2023)
Background: Pain management, a crucial part of nursing care, is considered one of the most basic patient rights. To properly treat patients pain, nurses need a high degree of pain management awareness (PMA). The researchers hypothesized that nurses pain management awareness is affected by their emotional intelligence (EI). Purpose: Because there is a dearth of studies on this topic, the purpose of this study was to describe the relationship between emotional intelligence and pain management awareness in a sample of nurses. Methods: The study employed a descriptive design with a quantitative approach to analyze data from a survey designed with the simple ran-dom sample technique. The questionnaires were completed by 330 nurses working at six govern-mental hospitals in Saudi Arabia. The Statistical Package for the Social Sciences (V23) and Analysis of Moment Structures (V23) were used to determine the reliability and validity of the questionnaires and analyze the causal relationships among the variables. Results: The results revealed a significant positive relationship between nurses emotional intelligence and their pain management awareness. Conclusions: These findings suggest that having emotional intelligence is an important nurse char-acteristic for effective pain management awareness and possibly the provision of pain management care. Clinical Implications: Hospital and nurse managers as well as administration should consider using the emotional intelligence variables utilized in this study to develop ways to improve pain management awareness among nurses. Such efforts may help improve hospital and patient outcomes related to pain management. 2022 by the authors. Licensee MDPI, Basel, Switzerland.